Valuation of Reset Option with Multiple Reset Features under Mixed Fractional Brownian Motion Model - Zhang, Xin (Journal of Global Economy, Business and Finance, 2024)
In this paper, we consider the pricing of reset option when the underlying asset follows a mixed fractional Brownian motion and the Hurst parameter H∈(0,1). Using quasi-martingale method, measure transformation and Girsanov theorem, the analytical expression of reset option pricing under risk neutral measure is obtained. The main contribution of this paper is to provide the closed-form pricing formula of reset option with strike resets and predetermined reset dates.